Dosimetry of laser-accelerated carbon ions for cell irradiation at ultra-high dose rate. (July 2020) - Milluzzo, G.; Ahmed, H.; Romagnani, L.; Doria, D.; Chaudhary, P.; Maiorino, C.; McIlvenny, A.; McMurray, A.; Polin, K.; Katzir, Y.; Pattathil, R.; McKenna, P.; et al.
Abstract: Charged particle radiotherapy is currently used in an increasing number of centres worldwide. While protons are the most widely used ion species, carbon ions have shown many advantages for the treatment of radioresistant tumours, thanks to their higher Linear Energy Transfer (LET) and Relative Biological Effectiveness (RBE). The complexity and the high cost of conventional carbon therapy facilities has stimulated the investigation of alternative acceleration approaches such as the processes based on high-power laser interaction with solid targets. Recent developments in ion acceleration have allowed to investigate for the first time the biological effects of carbon ions at ultra-high dose-rate (10 9 -10 10 Gy/s) using the GEMINI laser system at Rutherford Appleton Laboratory (RAL). Carbon ions were accelerated from ultrathin (10-20 nm) carbon foils and energy selected by a magnet allowing to irradiate the cells with an average carbon energy of 10 MeV/u ± 8%. A dosimetry approach specifically designed for these low-energy ions was employed, which was based on the use of unlaminated EBT3 Radiochromic films. The details of the dosimetry arrangement as well as the Geant4 simulation performed to predict the energy and the dose distribution at the cell plane will be reported.